No tempo dos tambores: os saberes ritmados pela infância na escola viva olho do tempo - Mendonça, Karla Jeniffer Rodrigues de (2018)
Learning as participatory action in childhood is the central theme of this dissertation. These actions were reflected and analyzed with the group "Tambores do Tempo" formed by children and adolescents having the teacher as principal regent; the group experiences the ?batuque? as a collective practice in percussion workshops at the OSCIP (Civil Society of Public Interest Organization) Escola Viva Olho do Tempo (EVOT), located in Gramame neighborhood, in the suburb of João Pessoa/PB. With the children the analyzes related to learning were (re) flourishing from their performance practices and experiences which I also engaged, revealing that the ?batuque?, at the time of the research, involved them in a participatory and nonclassificatory context in relation to their ages, as well as being a practice of interest for them. Based on these perceptions, this work flows through the studies of the childhood, striving to privilege the dialogue between the psychological, social, anthropological and educational theories. It was tried to understand how the learning happens for the children in the educational context of Evot trying to perceive how during the practices the children promoted their engagement and how the knowledge emerged in / with the body transformed the senses, the emotions and the movements, even those considered mechanical. It was worried to show how these actions were perceived by the children in intra and intergenerational relations, considering how the ways to learn and to share the knowledge in the environment emerged, noting how, in the relationship with things in context, the instruments, for example. That is why, with them, I experienced talk wheels, jokes, wandering and a lot of drumming, that is, the research developed from a participant and affective observation. I deal in this area with issues related to development, learning in / with practice and engaged actions considered autonomous. I conclude with the children that learning refers to knowing what arouses interest and presupposes intentionality, can happen as an act of autonomy in a heterogeneous way in collective relations in the environment, understanding as a process recognized in (in) corporating knowledge in a movement fluid and dynamic.